Pengembangan Aplikasi Voice Call Dengan Management Kontak Berbasis Suara Bagi Pengguna Tuna Netra - Guidita Suryani; Herman Tolle; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
With the existence of a smartphone allows everyone to communicate both verbal and non-verbal easier and can be done anytime and anywhere. However, people with visual impairments who have problems in a visual context feels difficult to operate a smartphone with a touch and flat screen. To overcome the problems experienced by visual impairments people in communicating using a smartphone, this research carried out a development of verbal communication applications for a voice calls that are also able to handle telephone contact management such as adding, changing contact data, and deleting a contact. This application is also designed specifically by using voice interaction that utilizes the Google API and allowing users to control the application by using voice and the feedback is also by voice. This application is design by using Human Centered Design (HCD) approach, which always involved the user in the development process. Based on usability testing using System Usability Scale (SUS), obtaining an average value of 86 which indicates the quality of the application is already at an